Respostas

2013-09-18T00:49:16-03:00
Você terá que utilizar a seguinte fórmula:
d= √(〖(x1-x2)〗^2+〖(y1-y2)〗^2)
Distância pm:
d= √(〖(x-3)〗^2+〖(y-6)〗^2)
d^2=〖(x- 3)〗^2 + 〖(y-6)〗^2
Distância pn:
d= √(〖(x-4)〗^2+〖(y-3)〗^2)
d^2=〖(x- 4)〗^2 + 〖(y-3)〗^2
Distância po:
d= √(〖(x-0)〗^2+〖(y-0)〗^2)
d^2=x^2 + y^2
Igualando as equações: 
〖(x- 3)〗^2 + 〖(y-6)〗^2= 〖(x- 4)〗^2 + 〖(y-3)〗^2
x^2 - 6x +9 + y^2 - 12y +36 = x^2 - 8x + 16 + y^2 -6y + 9
2x - 6y = -20
x- 3y = -10
E também:
〖(x- 3)〗^2 + 〖(y-6)〗^2 =x^2 + y^2
x^2 - 6x + 9 + y^2 - 12y +36= x^2 + y^2
-6x -12y = -45
2x + 4y= 15
Fazendo sistema
2x-6y=-20 e 2x+4y=15
-10y=-35
y=3,5
x=1/2

8 5 8